Pengaruh struktur GCG terhadap manajemen laba dengan koneksi politik sebagai variabel moderasi - Ismail Hasan; Puspita Rani (LPMP Imperium, 2024)
This research aimed to determine the influence of good corporate governance structure on earnings management with political connection as a moderating variable. The independent variables were managerial ownership, institutional ownership, board size, and independent commissioners. Earnings management was the dependent variable. The moderating variable was political connection. The research population was non-financial services companies listed on the Indonesia Stock Exchange 2018-2022. The research sample was 562 firm-years. The research results showed that institutional ownership and independent commissioners had a negative influence on earnings management, while managerial ownership and board size had no influence on earnings management. Political connection weakened the negative influence of institutional ownership on earnings management. Political connection was not proven to strengthen the positive influence of managerial ownership on earnings management. Political connection was not proven to weaken the negative influence of board size and independent commissioners on earnings management. Public interest statements This research can increase knowledge regarding GCG structures, political connection and earnings management. The results of this research can also be used as input for regulators in implementing GCG to prevent earnings management.